Pilot study of laser induced breakdown spectroscopy for tissue differentiation by monitoring the plume created during laser surgery - An approach on a feedback Laser control mechanism - Kanawade, Rajesh; Mehari, Fanuel; Knipfer, Christian; Rohde, Maximilian; Tangermann-Gerk, Katja; Schmidt, Michael; Stelzle, Florian (Spectrochimica Acta Part B-Atomic Spectroscopy, 2013)
This study focuses on tissue differentiation using 'Laser Induced Breakdown Spectroscopy' (LIBS) by monitoring the plasma plume created during laser surgery processes. This technique is aimed at controlling a laser surgery feedback system in real time. An Excimer laser (Ar-F 193 nm) was used for the ablation of tissue samples. Fat, muscle, nerve and skin tissue samples of bisected ex-vivo pig heads were prepared as test objects for the ablation procedure. A single fiber was used to collect emissions and deliver them to a spectrometer. The obtained LIBS spectra in the measured emissions were analyzed to determine each tissue type according to their chemical composition. The elements found in the samples and their emission spectra were in agreement with those described in literature. The collected LIBS spectra were analyzed to differentiate the tissues using statistical data analysis: Principal Component Analysis (PCA), Linear Discriminant Analysis (LDA) and Receiver Operating Characteristics (ROC). The obtained preliminary results suggest a successful differentiation of the target tissues with high sensitivity and specificity. The main goal of this study was to qualitatively identify tissue types during laser ablation, which will provide a real time feedback mechanism for clinical Laser surgery applications to significantly improve the accuracy and safety of laser surgery procedures. © 2013 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Chemical composition; Laser surgery feedback control; Plasma; Statistical method; Tissue differentiation